Spatial inhomogeneity and temporal dynamics of a 2D electron gas in interaction with a 2D adatom gas - F. Cheynis (Nature Portfolio, 2017)
Abstract Fundamental interest for 2D electron gas (2DEG) systems has been recently renewed with the advent of 2D materials and their potential high-impact applications in optoelectronics. Here, we investigate a 2DEG created by the electron transfer from a Ag adatom gas deposited on a Si(111) $$\sqrt{{\bf{3}}}{\boldsymbol{× }}\sqrt{{\bf{3}}}$$ 3 × 3 -Ag surface to an electronic surface state. Using low-energy electron microscopy (LEEM), we measure the Ag adatom gas concentration and the 2DEG-induced charge transfer. We demonstrate a linear dependence of the surface work function change on the Ag adatom gas concentration. A breakdown of the linear relationship is induced by the occurrence of the Ag adatom gas superstructure identified as Si(111) $$\sqrt{{\bf{21}}}{\boldsymbol{× }}\sqrt{{\bf{21}}}$$ 21 × 21 -Ag only observed below room temperature. We evidence below room temperature a confinement of the 2DEG on atomic terraces characterised by spatial inhomogeneities of the 2DEG-induced charge transfer along with temporal fluctuations. These variations mirror the Ag adatom gas concentration changes induced by the growth of 3D Ag islands and the occurrence of an Ehrlich-Schwoebel diffusion barrier of 155 ± 10 meV.